2021
DOI: 10.32629/jai.v4i1.483
|View full text |Cite
|
Sign up to set email alerts
|

Principle of Machine Learning and Its Potential Application in Cli-mate Prediction

Abstract: After two “cold winters of artificial intelligence”, machine learning has once again entered the public’s vision in recent ten years, and has a momentum of rapid development. It has achieved great success in practical applications such as image recognition and speech recognition system. It is one of the main tasks and objectives of machine learning to summarize key information and main features from known data sets, so as to accurately identify and predict new data. From this perspective, the idea of integrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…In recent years, machine learning methods have been used in climate prediction [16][17][18], and many successes in the prediction of sea surface temperature indexes beyond one year (>12 months) have been reported [19,20]. These successful applications of machine learning methods for predicting a climate phenomenon support this research work.…”
Section: Introductionsupporting
confidence: 52%
“…In recent years, machine learning methods have been used in climate prediction [16][17][18], and many successes in the prediction of sea surface temperature indexes beyond one year (>12 months) have been reported [19,20]. These successful applications of machine learning methods for predicting a climate phenomenon support this research work.…”
Section: Introductionsupporting
confidence: 52%
“…The CNN deep learning method commonly used in climate prediction [26,27] was used to obtain an extended-range forecast of RPECEs. Specifically, we predicted the time coefficient of low-frequency oscillations.…”
Section: Extended-range Forecastmentioning
confidence: 99%
“…In recent years, the rise of machine learning has provided new possibilities for numerical forecasting. Machine learning has been applied in climate prediction [2], and many scholars have used machine learning to conduct research and find applications in the field of storm surges. Lei [3] used the recurrent neural network (RNN) to forecast storm surges and found that it can obtain better prediction results than the backpropagation (BP) neural network.…”
Section: Introductionmentioning
confidence: 99%